Journalism and I vitamine - Masip, Pere (Anuario ThinkEPI, 2016)
Faced with the lost value of information that was traditionally produced by the press, audiences are now turning to social networks and interacting with the news in new ways. And, as a result, the low credibility of the Spanish media is negated by diversifying the sources for news information as people turn to their trusted gatekeeping "friends" who act as watchdogs of the fourth estate. For the moment this new relationship with social media does not mean a distancing from the news produced by professional journalists, but it does require that the media take steps to overcome the perceived loss in value of the information they produce.
Keywords: News; Journalism; Social Networks; Audience